(untitled) (Scientific journal of the Fergana State University, 2024)
The article talks about the perspective of the New Uzbekistan strategy, the institution of democratic management. Also, management is based on the principles of commitment to democracy and social justice. The state carries out its activities based on the principles of social justice and legality, aiming at the well-being of people and society. Also, governance as a political institution is based on pluralism. This is especially true in a democratic society. Therefore, the purpose of management in the new Uzbekistan is set at the constitutional level as "creating the well-being of man and society". Its basis is three: democracy, social justice and legality. These three concepts, in turn, form the basis of the responsibilities of management personnel.